Iatrogenic Left Main Bronchus Injury following Atraumatic Double Lumen Endotracheal Tube Placement. (31st October 2013) - Hartman, William R.; Brown, Michael; Hannon, James
Abstract : Tracheobronchial disruption is an uncommon but severe complication of double lumen endotracheal tube placement. The physical properties of a double lumen tube (large external diameter and length) make tracheobronchial injury more common than that associated with smaller single lumen endotracheal tubes. Here we present the case of an iatrogenic left main bronchus injury caused by placement of a double lumen tube in an otherwise unremarkable airway.